Nilai-Nilai Konfusius pada Tokoh Lu Yi 陆译 dalam Drama Under the Power（锦衣之下） - Berillya Imandika; Anitasa Dewi; Sri Hartati (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2022)
This research elucidates the drama Under the Power (锦衣之下Jǐnyī zhīxià) (2019), which narrates the journey of the main character Lu Yi (陆译) as an Embroidered-Uniform Guard (锦衣卫Jǐnyīwèi) of the Ming Dynasty (明朝Míng cháo) officiated with eradicating crime in the empire court. In every behavior, Lu Yi always shows his stand that adheres to the Confucian values, namely the Five Cardinal Virtues (五常Wǔ cháng) and the Eight Virtues (八德Bā dé). This research fathoms how far Confucius moral values are reflected in Lu Yi himself. Using the descriptive method and qualitative approach, the writer conducts a literature review on Confucius values and relates them to Lu Yi's character. From the research conducted, it is known that Lu Yi's character is indeed a notice enforcer who upholds the values of Confucius in himself, especially the value of defending truth and justice (义Yì). This drama has aired on Mango TV and iQiyi video platforms since December 28, 2019Keywords - Confucian values; Five Cardinal Virtues; Eight Virtues; Moral values; Drama; Television drama; Under the Power